Designing two-list group program driven algorithm for channel navigation in internet protocol television. (25th February 2020) - Adeliyi, Timothy T.; Olugbara, Oludayo O.
The internet protocol television took the advantage of the convergence of internet services to provide seamless interactivity, time shifting, video on demand and pay per view services. However, zapping delay is a critical problem that deters the switching intention of terrestrial subscribers and widespread of internet protocol television services. This article presents the design of an effective two-list group program driven algorithm that minimises the channel seek distance and channel seek time in order to reduce zapping delay in internet protocol television. The algorithm groups similar channel programs in related service categories such as news, movies, sports, music and documentary to make it easier for channels with similarly aired programs to be identified rapidly among several channels that an internet protocol television offers. The simulated results of the proposed algorithm show that the average seek distance is significantly reduced by 58% when benchmarked with the state of the art numerical ordering, frequency circular ordering and frequency interleaved ordering.